Absorption properties of TiO2 coated MWCNT/FE3O4/poly aniline Nano composite in x-band - Esmaeili, Saba; Sedghi, Hassan (International Journal of Engineering and Technology, 2019)
The aim of current research is construction and investigation of radar absorbing material (RAM) -TiO2@MWCNT/Fe3O4/PANI nano composite. In order to construction of nano composite sample; we prepare 20% weight of TiO2@MWCNT nano fillers (by sol gel method) , Fe3O4 and PANI in separate form and then we used proper solution in ultrasonic bath by adding epoxy resin and hardener with nano composite solution blending method in X band standard size (22.8*10.16 mm2) and 3mm thickness. Phase and morphology features were investigated by X ray diffraction analysis and Scanning electron microscopy. RAM- TiO2@MWCNT/Fe3O4/PANI nano composite mi-crowave features were studied at X band at the range of 8-12 GHz by vector network analyzer. Reflection loss has two minimum peak such as -28.59 dB at 9.36 GHz and -33.77 dB at 10.9 GHz. Electromagnetic parameters such as permeability, permittivity, tangent loss and refractive coefficient were studied. Results showed that using proper nano fillers to combining dielectric and magnetic losses microwave absorption increasing.Â